2013
DOI: 10.3109/01612840.2013.824053
|View full text |Cite
|
Sign up to set email alerts
|

PTSD in Psychiatric Nurses and Other Mental Health Providers: A Review of the Literature

Abstract: Psychiatric nurses are subject to a high rate of assault by patients. The stress of exposure to assault and the potential for assault appear to impact nurses' emotional states in the form of post-traumatic stress and post-traumatic stress disorder (PTSD). Most studies report a prevalence rate of PTSD in this population of between 9-10%. Training in the management of aggressive patients, participating in Critical Incident Debriefing, and having routine structured debriefing meetings may play a role in facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 37 publications
2
58
1
1
Order By: Relevance
“…). Further, existing research draws attention to the incidence of posttraumatic stress in nurses working in acute psychiatric inpatient settings being about 10% (Jacobowitz ). In short, working in acute inpatient units and EDs is stressful.…”
Section: Discussionmentioning
confidence: 99%
“…). Further, existing research draws attention to the incidence of posttraumatic stress in nurses working in acute psychiatric inpatient settings being about 10% (Jacobowitz ). In short, working in acute inpatient units and EDs is stressful.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, for example, over a 12‐month period 76% of mental health nurses reported depressive symptoms (Hsieh et al . ) and up to 10% of mental health nurses report post‐traumatic stress disorder (Jacobowitz ). The emotional labour of dealing with challenging interpersonal situations with consumers, families, and colleagues can also lead to emotional dissonance (Delgado et al .…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative effects of workplace violence and workload demands can contribute to chronic stress and mental distress (Lanctôt & Guay 2014), and lower mental health. In a recent study, for example, over a 12-month period 76% of mental health nurses reported depressive symptoms (Hsieh et al 2017) and up to 10% of mental health nurses report post-traumatic stress disorder (Jacobowitz 2013). The emotional labour of dealing with challenging interpersonal situations with consumers, families, and colleagues can also lead to emotional dissonance (Delgado et al 2017;Edward et al 2017) and substantial levels of burnout (up to 67%; Morse et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…). Consequently, in the UK, since the late 20th century, violence and aggression has substantially increased (Bilgin & Buzlu ) and presents serious hazards for the safety and well‐being of healthcare professionals (Jacobowitz ).…”
Section: Introductionmentioning
confidence: 99%